2015
DOI: 10.1007/s00590-015-1624-3
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the use of allogeneic blood products in adolescent idiopathic scoliosis surgery

Abstract: Since February 2012, no patient has required intraoperative or postoperative allogeneic blood product transfusion in this hospital. The routine use of antifibrinolytic medications in patients undergoing surgery for adolescent idiopathic scoliosis has effectively eliminated the need for allogeneic blood products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Typically, any intervention evaluated in a randomized controlled trial only reduces more than 25%, which calls for attention. [11,13,14] The 13% reduction of the total blood loss could not provide reliable evidence for the usage of TA. The present study manifested administering 30 mg/kg initial dose and 2 mg/kg/h maintenance dosage, which lessened 41% total blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, any intervention evaluated in a randomized controlled trial only reduces more than 25%, which calls for attention. [11,13,14] The 13% reduction of the total blood loss could not provide reliable evidence for the usage of TA. The present study manifested administering 30 mg/kg initial dose and 2 mg/kg/h maintenance dosage, which lessened 41% total blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Previous studies demonstrated that TA could inhibit the fibrinolytic activity and decrease blood loss in spinal deformity surgery or long segment fixation and fusion surgery. [9,1113,25] Elwatidy et al [25] showed that TA reduced 49% blood loss in the spinal surgery. Berney et al [11] reported that TA decreased nearly 50% intraoperative estimated blood loss in adolescent idiopathic scoliosis surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations